Through the Heart of Dixie : Sherman's March and American Memory - Rubin, Anne S. (Civil War America (Series), 2014)
"Sherman's March, cutting a path through Georgia and the Carolinas, is among the most symbolically potent events of the Civil War. In Through the Heart of Dixie, Anne Sarah Rubin uncovers and unpacks stories and myths about the March from a wide variety of sources, including African Americans, women, Union soldiers, Confederates, and even Sherman himself. Drawing her evidence from an array of media, including travel accounts, memoirs, literature, films, and newspapers, Rubin uses the competing and contradictory stories as a lens into the ways that American thinking about the Civil War has changed over time".